Manejo de aceites lubricantes usados y criterios de calidad química del suelo de la lavadora & lubricadora Vélez del cantón Chone - Torres Muñoz, Roberth Emilio (2021)
The objective of this research was to evaluate the handling of lubricating oils used in the Vélez Washer and Lubricator in Chone canton. This is a descriptive, non-experimental - quantitative investigation, with analytical and synthetic methods, applying observation, interview and checklist techniques. For the purpose of this work, a diagnosis of the current situation of the management of used lubricating oils was carried out. Subsequently, the determination of the criteria of chemical quality of the floor of the Velez Washer and Lubricator was carried out. Finally, a guide to good environmental practices was drawn up for the correct handling of lubricating oils. The results showed through the interview and the checklist that the establishment does not comply with current environmental regulations, establishing 80% non-compliance. Soil analyzes showed that Total Petroleum Hydrocarbons, Polycyclic Aromatic Hydrocarbons and Cadmium are above the maximum permissible limits with values of 31458.96 - 6.63 and 0.78 mg / kg respectively. A guide to good environmental practices for the management of used lubricating oils was socialized.